Rancang Bangun Aplikasi Virtual Tour Berbasis Android untuk Pariwisata Pulau Belitung sebagai Media Informasi - Fathurrahman, Ade; Firdaus, Diky (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Information Technology is expected to be a solution in tourism, especially in Belitung Island. The purpose of this study is to make it easier for tourists visiting Belitung Island to easily determine the tourist locations to be visited by showing the closest tourist locations and also virtual tours of each of the available tourist attractions. The method used in this research is the Multimedia Development Life Cycle (MDLC) method. This research was made so that tourists can easily determine the destination of tourist attractions based on the distance from the tourist location and virtual tours that utilize 360-degree images on the android application. At the search stage, the application will ask for gps access to see the starting point of the tourist. Then the system will automatically provide a list of tourist attractions sorted by the closest distance to tourists. Then after the tourist chooses a tourist spot, the application will bring up the details of the tourist spot and give the option to bring up a virtual tour of the tourist spot. With the addition of virtual tours and the Haversine formula for determining distances through the longitude and latitude of a location, it has proven to be effective in providing the detailed information travelers need.